Two-Dimensional calcium silicate nanosheets for trapping atmospheric water molecules in humidity-immune gas sensors - Cho, Young Ju; Kwon, Yong Jung; Jin, Sunghwan; Choi, Hyeunseok; Lee, Jung-Hoon; Yang, Seung-Min; Choi, Sun-Woo; Jeong, Young Kyu (Elsevier BV, 2022)
In humid conditions, water vapor can easily neutralize the surface active sites of metal oxide sensors, leading to a lowering in the sensitivity of the gas sensor and a resultant inaccurate signal in practical applications. Herein, we present a new hybrid sensor by introducing a two-dimensional calcium silicate (CS) nanosheet as a water trapping layer in SnO2 nanowires. Unlike the heavily wrinkled and aggregated morphology of conventional CS nanosheets, our nanosheet in the hybrid material is ultrathin and flat. Moreover, it was grown in the empty spaces between the spider-web-like networks of SnO2 nanowires without covering the nanowire surface. These two morphological features improve moisture trapping with minimal reduction in the active sensing area. Consequently, stable and sensitive gas detection under humid conditions was achieved in this hybrid sensor. The superior humidity-independent sensing is ascribed to the preferential adsorption of water molecules on hydroscopic CS nanosheets through the hydrogen bond. Based on density functional theory calculations, we determined that the improved gas response is driven by the additional formation of oxygen vacancy in SnO2 due to the diffusion of aliovalent Ca ions from the CS nanosheet.